Cold-hot nature identification of Chinese herbal medicines based on the similarity of HPLC fingerprints - Wei, Guohui; Jia, Ronghao; Kong, Zhiyong; Ji, Chengjie; Wang, Zhenguo (Frontiers in Chemistry, 2022)
The nature theory of Chinese herbal medicines (CHMs) is the core theory of traditional Chinese medicine (TCM). Cold-hot nature is an important part of CHM nature. It is found that the material basis of cold-hot nature is CHM ingredients. To test the scientific hypothesis that "CHMs with similar cold-hot nature should have similar material basis", we explored an intelligent method for cold-hot nature identification of CHMs based on the feature similarity of CHM ingredients in this work. 61 CHMs were selected for cold-hot nature identification. High performance liquid chromatography (HPLC) was used to separate the chemical ingredients of CHMs and extract the feature information of CHM ingredients. A distance metric learning algorithm was then learned to measure the similarity of HPLC fingerprints. With the learned distance metric, cold-hot nature identification scheme (CHNIS) was proposed to build an identification model to evaluate the cold-hot nature of CHMs. A number of experiments were designed to verify the effectiveness and feasibility of the proposed CHNIS model. The total identification accuracy rate of 61 CHMs is 80.3%. The performance of the proposed CHNIS algorithm outperformed that of the compared classical algorithms. The experimental results confirmed our inference that CHMs with similar cold-hot nature had similar composition of substances. The CHNIS model was proved to be effective and feasible.